The Efficiency and Safety of Transperitoneal versus Extraperitoneal Robotic-Assisted Radical Prostatectomy for Patients with Prostate Cancer: A Single Center Experience with 1-year Follow-up - Yang, Yubo; Liu, Zhenhua; Guo, Yaochuan; Li, Xiang; Liu, Liangren; Wang, Xiaoming; Bai, Yunjin; Wei, Qiang; Han, Ping (Urology Journal, 2020)
Purpose: Several studies have compared the short-term outcomes of extraperitoneal robot-assisted laparoscopic radical prostatectomy (EP-RALP) and transperitoneal RALP (TP-RALP). The study was designed to evaluate the long-term outcomes of the two methods. Materials and Methods: A prospective, non-randomized study was conceived. The demographics and operative outcomes of patients with prostate cancer undergoing RALP from September 2016 to January 2017 at our center were included. Results: A total of eighty-six patients were enrolled. Thirty-seven patients underwent EP-RALP, and forty-nine patients received TP-RALP. No significant difference was observed in age, body mass index, pathological T stage, pathological N stage, M stage, 2014 International Society of Urological Pathology group, comorbidities or American Society of Anesthesiologists score. A lower preoperative prostate-specific antigen (PSA) was detected in the EP-RALP group. No significant differences were observed in overall operation time, robotic console time, surgical margin status, postoperative hospitalization time, drop of hemoglobin and complications, except that patients with EP-RALP had a shorter time to first exsufflation after surgery than those with TP-RALP (41.35 vs. 51.80 h, P < .001). Postoperative PSA until 12 months was deemed comparable in both groups. Complete continence until 12 months after surgery was desirable but not significantly different between two groups (75.0% in EP- RALP vs. 86.7%. in TP-RALP, P = .179). Conclusion: The long-term outcomes of EP-RALP were analogous to those of TP-RALP. Therefore, EP-RALP is an alternative approach for patients with localized prostate cancer. Keywords: prostate cancer; robot-assisted prostatectomy; extraperitoneal approach; transperitoneal approach; enhanced recovery after surgery